2015
DOI: 10.1016/j.aucc.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Early rehabilitation in the intensive care unit: An integrative literature review

Abstract: A limited body of research supports early rehabilitation interventions to optimise the short term outcomes and long term quality of life for ICU survivors. Critical care nurses are in an excellent position to drive change within their departments ensuring that early rehabilitation practices are adopted and implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 45 publications
(188 reference statements)
3
41
0
8
Order By: Relevance
“…The study also revealed that physical therapists in the participating hospitals neither agree nor disagree regarding the prioritization of service, adequate consultations, or adequacy of perceived importance by other healthcare providers for the role of physical therapists as healthcare professionals who are capable to work in an ICU setting. Despite the expanding evidence on the importance of physical therapy for intensive care patients that is reflected on improving physical condition (Bailey et al, ; Burtin et al, ; Morris et al, ; Schweickert et al, ), quality of life (Sosnowski, Lin, Mitchell, & White, ), shorter length of stay in ICU or in hospital (Kayambu, Boots, & Paratz, ), and on decreased financial costs (Lord et al, ), our results of physical therapy service prioritization in the ICU setting, consultations, and the adequacy of perceived importance clearly indicate barriers in physical therapy practice in the ICUs of participating hospitals. Perhaps, the unstable physiological condition of patients and the unpredictability that might have been encountered by these patients give less priority to physical therapist to take part in decision making.…”
Section: Discussionmentioning
confidence: 74%
“…The study also revealed that physical therapists in the participating hospitals neither agree nor disagree regarding the prioritization of service, adequate consultations, or adequacy of perceived importance by other healthcare providers for the role of physical therapists as healthcare professionals who are capable to work in an ICU setting. Despite the expanding evidence on the importance of physical therapy for intensive care patients that is reflected on improving physical condition (Bailey et al, ; Burtin et al, ; Morris et al, ; Schweickert et al, ), quality of life (Sosnowski, Lin, Mitchell, & White, ), shorter length of stay in ICU or in hospital (Kayambu, Boots, & Paratz, ), and on decreased financial costs (Lord et al, ), our results of physical therapy service prioritization in the ICU setting, consultations, and the adequacy of perceived importance clearly indicate barriers in physical therapy practice in the ICUs of participating hospitals. Perhaps, the unstable physiological condition of patients and the unpredictability that might have been encountered by these patients give less priority to physical therapist to take part in decision making.…”
Section: Discussionmentioning
confidence: 74%
“…Besonders in der Herzchirurgie verkürzen sich Intensiv und Krankenhausaufenthalt durch physikalische Therapiemaßnahmen signifikant [22]. Gesamtstatus verbessert werden kann und auch die Folgen der critical illnessPolyneuropathie signifikant reduziert werden können [29].…”
Section: Verfügbare Wissenschaftliche Evidenzunclassified
“…Eine Einbindung gut ausgebildeter Therapiespezialisten ins interprofessionelle und interdisziplinäre Team der Intensivstation ist dabei wichtig. Aus den betrachteten Arbeiten geht außerdem hervor, dass eine hervorragende Sicherheit und Anwendbarkeit der rehabilitativen Verfahren auf der Intensivstation besteht [9,29]. In einer systematischen Literaturanalyse kommt auch zu der Schlussfolgerung, dass die physikalisch medizinische/rehabilitative Therapie bei beatmeten Patienten sowohl sicher und durchführbar ist als auch die Weaningphase unterstützen kann [19].…”
Section: Verfügbare Wissenschaftliche Evidenzunclassified
“…Longitudinal studies on critical illness survival show that 30-80% of patients will acquire PICS, characterised as a collection of complications including persistent cognitive dysfunction, acquired weakness and post-traumatic stress disorder [4,5]. A substantial proportion of patients who survive their initial critical care stay, report significant decreases in quality of life at 6 months post admission [6] in addition to increased mortality and associated economic costs [7][8][9] Early rehabilitation within critical care settings is now considered effective and feasible when carried out within a multidisciplinary approach [11][12][13]. Thus, while physical rehabilitation and early cognitive stimulation have been shown to be effective, to date there remains little evidence regarding the impact of early task-specific training carried out by occupational therapists directed towards cognitive and functional engagement.…”
Section: Introductionmentioning
confidence: 99%